Anti-ulcerogenic effect of methanol fraction of Ocimum gratissimum leaves extract and honey on indomethacin-induced gastric ulcer in rats. Issue 1 (1st January 2021) - Salemcity, Aanuoluwa James; Omolaso, Blessing Oluwagbamila; Ogegere, Oghenefega Sheila; Oluokun, Victoria Olasumbo
ABSTRACT: Ocimum gratissimum (Og), a medicinal plant, and honey (H), a natural sweetener usually produced by bees, have historic importance in managing several ailments. This study aims at unraveling the anti-ulcerogenic effect of methanol leaves fraction (MEF) of Og and H on indomethacin-induced gastric ulcer in male rats. Crude methanol extract was partitioned between hexane, chloroform, ethylacetate and methanol successively using vacuum liquid chromatography. The anti-ulcerogenic effect of MEF of Og (100 and 400 mg/kg), honey (2.5 g/kg) and their combination was determined using indomethacin-induced gastric ulcer model. Gastric acidity, antioxidant assays and histopathology were conducted via titrimetric, spectrophotometric, H&E stain with microscopy methods respectively. Significant difference ( P < 0.05) existed in ulcer score and gastric pH in all groups except MEF pre-treated relative to control. Significant increase and decrease existed in MDA level in untreated and pre-treated groups successively compared to control. CAT activity displayed no significant difference in 400 mg/kgMEF and 400 mg/kg/2.5 g/kgH proportionate to control. GST activity showed significant elevation in pre-treated groups compared to control. Meanwhile, GPx activity increased in 400 mg/kg MEF and 400 mg/kgMEF/2.5 g/kgH relative to control. There was no significant difference in TSH status in the pre-treated groups relative to control. Mild inflammatory cellular infiltration in the sub-mucosal layers in pre-treated groups occurred. The data suggests MEF effectively prevented ulcer better than fortification with honey and honey used singly. GRAPHICAL ABSTRACT: uf0001